DogPerfect, Second Edition : - Hodgson, Sarah (Wiley Pub., 2003)
Your dog will learn how to Sit, Stay, Settle Down, Come and Heel like the well-mannered companion you want him to be. DogPerfect is a positive, unintimidating guide that can help any dog owner–especially when the pooch in question is less than perfect. You'll discover how to: Use clicker, target and point training to spice up your lessons. Stop your dog from pulling you down the street. Teach your dog to Sit while greeting company. Play fun and instructional games with your dog. Handle problem barking, chewing, jumping and much more!